UJI AKTIVITAS ANTIMIKROBA EKSTRAK UMBI BAWANG DAYAK (Eleutherine americana Merr.) TERHADAP Propionibacterium acne BAKTERI PENYEBAB JERAWAT DAN POTENSINYA SEBAGAI RANCANGAN LKPD PADA MATERI KINGDOM MONERA KELAS X SMA - Latifah Latifah; Yustina Yustina; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted to determine the effect of the chemical compounds of Dayak onion (Eleutherine americana Merr.) Root extract against Propionibacterium acne bacteria that cause acne which is used in designing students' worksheets on kingdom monera class X high school material conducted in December 2019 - February 2020 in University of Riau PMIPA Chemistry Laboratory, University of Riau Biology PMIPA Laboratory and Pekanbaru Regional Health Laboratory. This research is an experimental laboratory study using the method of diffusion of wells on BAP (Blood Agar Plate) media with 4 treatments. The treatment was repeated 3 times with various concentrations of 30%, 50%, 70%, and 90% and terracycline was used as a comparison and distilled water as a control. This study used a laboratory experimental method. The parameters observed were the characterization of Propionibacterium acne bacteria, the diameter of the inhibitory zone of Propionibacterium acne growth bacteria and the potential results of the study as a design of Class X Biology LKPD in Kingdom Monera material. Analysis of research data using One Way Anova at the 0.05 level. The results showed the characteristics of white, round shaped bacterial colonies and on microscopic observations of bacterial stem cells. In physiological characterization found the characteristics of the positive salt-colored salt bacteria, positive catalase, non-motile and positive indole. Whereas in measuring the diameter of the zone of inhibition of the growth of P. acne, tuber extract of dayak has the ability to inhibit the growth of P. acne bacteria at the best concentration of 90% with an average diameter of inhibition zone of 19 mm within 48 hours. The results obtained were then used as a draft LKPD on KD 3.5 and KD 4.5 kingdom monera material class X high school. Keywords: Characteristics, Eleutherine americana Merr., Propionibacterium acne, Student worksheet.